Loyalty Reflected At Henrik Ibsen's (1882) Drama: An Individual Psychological Approach - Sadewo, Aji Setiawan Wahyu (2016)
The major problem of this study is loyalty. Someone who suddenly has loyalty nature, she must confront the problem persist struggled. The objective of this study is to analyze Henrik Ibsen's Public Enemy based on the structural elements and analyze this drama based on the Individual Psychological Approach.The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is Public Enemy drama by Henrik Ibsen. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the drama. The secondary data of the study are taken from any information related to the drama.The method of data collection is the reseacher will employ the descriptive qualitative research.Based on the analysis, the reseacher gets some conclusions. The study shows that the problem faced by the minor character is her loyalty. It is proven by his dream that becomes success. She is a housewife. She wants to live normally without any problems with her family. Someday, Dr. Stockmann gets big news for the town. But, the Mayor didn't agree with that news, so Mrs. stockmann worry, so she tells it to her husband. Then her husband was betrayed by hovstad and aslaksen. Finally, Mrs. stockmann remains faithful to Dr. Stockmannn.